Pumpkin seed oil attenuates colchicine-induced splenic injury: Evidence from oxidative stress, immune, and apoptosis-related biomarkers - Yasmina M. Abd-Elhakim; Manar A. AbdelMageed; Taghred M. Saber; Nabela I. El-Sharkawy; Gihan G. Moustafa; Fathy Elsayed Abdelgawad; Bayan A. Hassan; Taisir Saber; Hayaa M. Alhuthali (Tissue and Cell, 2027)

The interplay of bosentan and finerenone in amelioration of cardiac dysfunction within benign prostatic hyperplasia in rats - Marwa Monier Mahmoud Refaie; Asmaa A. Hasan; Asmaa A. Muhammed; Randa Ahmed Ibrahim; Eman Abdel Naby Hassan; Enas Fathy; Aml Mohamed Soliman; Hoda S. Sherkawy; Olivia N. Beshay; Amr Alam-Eldin Ahmed; Ahmed Ahmed; Samar Hisham Elsayed; et al. (Molecular Biology Reports, 2026)

Immunohistochemical expression of JAK2, STAT3, POLH, UBE2T, and REV7 in serous ovarian carcinoma: clinicopathological associations and co-expression patterns - Mayada Saad Farrag; Rokia Masoud; Mohamed S. Hemeda; Ziad Emarah; Khaled El Naghy; Khaled Abdelwahab; Nesrine Saad Farrag; Afaf Taha Ibrahiem; Ziad Ehab; Waleed Elsayed Elrefaie; Ahmed Elalfy; Mohamed K. Hassan (Journal of Molecular Histology, 2026)

A Novel Green MIP-202/TOCNF Composite Aerogel for Rapid PFAS Adsorption: Performance, Kinetics, and Mechanistic Insights - Muhammad Hamza; Muhammad Waqas; Islam Elsayed; Gregory Schueneman; El Barbary Hassan (Journal of Environmental Chemical Engineering, 2026)

Fisetin promotes liver regeneration by inducing β-catenin-mediated inhibition of p53 and suppression of TGF-β - Ghada Ibrahem Draz; Huda El-Tahry; Rania Naem Sherif; Amira Elsayed Farage; Randa El-Gamal; Ahmed Mohammed Elsabbagh; Hassan Reda Hassan Elsayed (Tissue and Cell, 2026)

Mechanistic Insights into Honey-Mediated Antibacterial Activity Against Enterobacteriaceae: A Multifaceted Approach Targeting Membrane Integrity, Protein Synthesis, and Quorum Sensing Inhibition - Mervat G. Hassan; Naseh A. Algehainy; Batul Hatem Ghoniem; Faisal H. Altemani; Ashraf Elsayed; Hanaa Ghabban; Alaa Elmetwalli (Probiotics and Antimicrobial Proteins, 2026)

Innovative synbiotic functional fermented barley-based milk using novel isolated probiotic Levilactobacillus brevis HBE2 and Enterococcus faecalis HBE4 - Hany Elkashef; Nesren Elsayed; Awad A. Awad; Ashwak Abdel Moneim Hassan (Innovative Food Science & Emerging Technologies, 2026)

Toward Eco-Friendly Solutions for Plastic Pollution: Insights into Polyethylene Biodegradation - Alaa F. Elsayed; Dina H. Amin; Hassan M. Gebreel; Ihsan Mahasneh; HebatAllah I. Youssef (Water, Air, & Soil Pollution, 2026)

Bridging food and clinical neurotherapeutics in ADHD management: A comprehensive comparative evidence on phytochemicals and non-pharmacologic paradigms - Eman Maher Zahran; Aliaa Gamal; Motaz M. Hassan; Mohamed M. Elsayed; Eyad Y. Elhamadany; Nursin Mustafa Bayoumi; Tarek Gamal Ebrahim; Fatma Alzahraa Mokhtar; Islam M. Abdel-Rahman; Hesham A. Abou-Zied; Usama Ramadan Abdelmohsen (Food Bioscience, 2026)

Unveiling Morpho-Anatomical Strategies of Cenchrus Ciliaris L. for Survival under Vehicular Pollution Stress - Hafiz Muhammad Mohsin Hassan; Muhammad Akram; Imran Haider; Muhammad Altaf Nazir; Lamy Hamed; Abdullateef Al-Saeed; ElSayed A. Badr; Ahmed Ismail (Water, Air, & Soil Pollution, 2026)

Impact of nano-selenium supplementation on in vitro gas production, methane mitigation, and in vivo performance of Ossimi Egyptian Sheep - Hamdy Mohamed Khattab; Ahmed Zaki El-Basiony; Salwa Mahmoud Hamdy; Mahmoud Hassan; Nasr Elsayed El-Bordeny; Osama Mohamed Darwesh; Gamal Ali Elsayaad; Raafat Mahmoud Mohamed Gomaa (Tropical Animal Health and Production, 2026)

Optimizing Domestic Wastewater Treatment Using Moringa Oleifera Lam. Vegetated Constructed Wetlands: A Case Study et al.-Habil Wastewater Treatment Plant, Luxor - Naira Meky; Raouf Hassan; Mohamed F. Soliman; Aml Mahmoud; Mahmoud Elsayed (Water, Air, & Soil Pollution, 2026)

Investigation of the Antibacterial Effectiveness of Hybrid Recombinant Bacteriocins Circular Enterocin and Pyocin L1 Derived from Pseudomonas aeruginosa and Enterococcus faecalis - Lina Jamil Abdel-Hafez; Mohamed Salah Basiouny; Islam Yousif Mostafa; Rehab Moustafa; Khaled Abuelhaded; Haytham Mohamed Abd-Elhalim; Abanoub A. S. Shaker; Hassan Elsayed; Olfat Salem; Amir Mahfouz Mokhtar Sarguos; Ahmed Hassan Ibrahim Faraag (Biochemical Genetics, 2026)

Microbial decontamination and enhanced extraction of value-added compounds from Spirulina platensis using gamma radiation - Hamdy Elsayed Ahmed Ali; Mohamed S. Abd El-AL; Marwa M. Moussa; Ola M. Gomaa; Kamal A. Hassan; Eman A. El-fayoumy (World Journal of Microbiology and Biotechnology, 2026)
Spirulina platensis has garnered increasing attention as a valuable source of proteins, lipids, and pigments, with applications in the food, feed, and nutraceutical industries. However, large-scale cultivation in open pond systems is liable to microbial contamination, posing risks to product quality and productivity. This study evaluated the effects of gamma (γ) irradiation up to 10 kilogray (kGy) as a dual strategy for microbial decontamination and enhanced extraction of bioactive compounds from dried Spirulina powder. A dose of 4 kGy resulted in a substantial reduction in microbial populations, while irradiation at 6 kGy reduced microbial counts to levels below the detection limit of the applied culture-based methods, indicating effective decontamination. The D₁₀-values obtained for Bacillus sp. (0.44 kGy), Staphylococcus aureus (0.41 kGy), and Pseudomonas aeruginosa (0.58 kGy) demonstrate species-dependent radiosensitivity. Analyses using electron spin resonance (ESR), UV–Vis spectroscopy, Fourier transform infrared spectroscopy (FTIR), and lipid peroxidation assays demonstrated that γ-irradiation preserved the structural integrity of key biomolecules. Biomass irradiated at 6 kGy exhibited the highest recovery of lipid (60.83 ± 1.38 mg g⁻¹), protein (547.43 ± 2.97 mg g⁻¹), and carbohydrates (275.60 ± 2.50 mg g⁻¹). Pigment extraction also increased, yielding elevated levels of chlorophyll a (11.40 ± 0.10 mg g⁻¹), carotenoids (3.48 ± 0.30 mg g⁻¹), and phycobiliprotein (125.20 ± 0.70 mg g⁻¹). Antioxidant activity peaked at 69.61 ± 1.47% at the same dose, associated with enhanced phenolic content. Overall, γ-irradiation represents a promising biotechnological tool for producing microbiologically safe Spirulina biomass while improving the extraction of value-added bioactive compounds for nutraceutical and pharmaceutical applications.

Adaptive morphological and physiological strategies of Sporobolus ioclados in desert ecosystem - Muhammad Akram; Nargis Naz; Ummar Iqbal; Syeda Refat Sultana; Fahim Arshad; Muhammad Waheed; Muhammad Adeel Ghafar; Hafiz Muhammad Mohsin Hassan; Arslan Asghar; Abeer Hashem; Dalal Saad Alharbi; Graciela Dolores Avila-Quezada; et al. (The Science of Nature, 2026)

Maternal high-fat diet and its multigenerational impact on hypertension and metabolic alterations in Wistar rat offspring - Maghawry Hegazy; Mahmoud Mohamed Mokhtar; Elsayed G. E. Elsakka; Hesham A. El-Mahdy; Samy Y. Elkhawaga; Mohamed A. Elkady; Amr Mohamed Yehia; Ahmed Aglan; Ahmed M. Mansour; Salama Abdo Salama; Hamada Ahmed Mokhlis; Hesham Fathy Hassan; et al. (Journal of Molecular Histology, 2026)

Talc mineralization in the SW Fodikwan area, Red Sea Hills, NE Sudan: Geological and geochemical constraints - Alsir A.A. Alkhaleefa; Talha M. Yousif; Musab A.A. Hassan; Khalid A. Elsayed Zeinelabdein (Journal of African Earth Sciences, 2026)

Experimental investigation of ultrasonic water injection effects on laminar flame characteristics of propane-air mixtures - Elsayed Barakat; Hui Wang; Haroun Hassan; Chenghao Qian; Jing Hou; Tai Jin; Gaofeng Wang (Fuel, 2026)

Zero Liquid Discharge Performance in Complex Fertilizer Industry Wastewater Treatment - Mahmoud Elsayed; Abdelrahim M. Abdeldaim; Mohamed F. Soliman; Raouf Hassan; Naira Meky (Water, Air, & Soil Pollution, 2026)

Recent strategies and methodological advances for microbial natural product research in the post-genomics era - Abdelrahman M. Sedeek; Mariam Hassan; Tarek R. Elsayed; Mohamed A. Ramadan (Archives of Microbiology, 2026)

Sustainable Africa space governance: Strategic decision support framework, opportunities, challenges and solutions - Rania Elsayed Ibrahim; Alaaeldin S. Hassan; Tshiamo Motshegwa (Journal of Space Safety Engineering, 2025)

Exploring the Link Between IL-6 rs1800795 G > C SNP and the Severity of Epstein-Barr Virus-Associated Multiple Sclerosis: Potential Impact on Cognitive Impairment - Tokka M. Hassan; Azza M. El Amir; Nahla Elsayed Nagy; Nashwa El-Khazragy (Molecular Neurobiology, 2025)
Multiple Sclerosis (MS) is a chronic immune-mediated neurological disorder frequently accompanied by cognitive impairment, which affects up to 60% of patients and is associated with faster disease progression and greater disability. Interleukin-6 (IL-6), a key proinflammatory cytokine involved in neuroinflammation, has been implicated in MS pathogenesis, and the rs1800795 (−174 G>C) single nucleotide polymorphism (SNP) in the IL6 gene may influence disease susceptibility and clinical severity. This study investigated the association between the IL6 rs1800795 polymorphism and clinical outcomes in Epstein-Barr virus (EBV)-positive MS patients, with a particular focus on cognitive dysfunction. A case-control design was employed, including 300 participants: 150 EBV-positive MS patients and 150 matched healthy controls. Genotyping was performed using TaqMan-based PCR, and clinical data such as disability status, disease progression, and cognitive performance were analyzed. The CC genotype was significantly more frequent in MS patients and was associated with a higher risk of severe disability (OR = 6.11, p = 0.0004), faster disease progression, and increased likelihood of cognitive impairment. These findings suggest that the IL6 rs1800795 polymorphism, particularly the CC genotype, contributes to MS susceptibility and adverse clinical outcomes. IL6 genotyping may hold promise as a predictive tool for disease progression and cognitive decline in EBV-associated MS, offering insights for more personalized therapeutic strategies.

Dietary spirulina platensis a promising growth promotor and immune stimulant in broiler chickens - Enas Mahmoud; Gehad Elsayed; Azza Hassan; Ahmed Ateya; Shimaa Abd El-Salam El-Sayed (Natural Product Research, 2025)

Protective role of curcumin and selenium nanoparticles against aluminium chloride-induced hepatorenal toxicity in rats - Safaa M. Awad; Yasser A. Attia; Akaber T. Keshta; Shimaa H. Watad; Eman Rashad; Hassan Elsayed; Shams H. Abdel-Hafez; Aziza T. Fathy (Journal of Molecular Histology, 2025)

Liraglutide mitigates dexamethasone-induced fatty acid synthase (FASN) and the cluster of differentiation36 (CD36) expression: a potential treatment for glucocorticoid-induced non-alcoholic fatty liver disease (NAFLD) - Dahshan Hassan Selim; Hamada Ahmed Mokhlis; Abdelrahman M. Elsayed; Abdel-Aziz S. Shatat; Salama Abdou Salama; Raed Shahat Ismail (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
The clinical use of dexamethasone (DXM) is associated with the development of non-alcoholic fatty liver disease (NAFLD). However, the mechanisms by which DXM-induced NAFLD is still incompletely known. Therefore, the current study aims to test the hypothesis that DXM-induced NAFLD is mediated by dysregulation of key genes involved in lipid metabolism and liraglutide (LG) can ameliorate these effects. The histopathological and biochemical analysis assessed the effects of DXM and/or LG in liver tissue. The computational analysis was performed to detect the glucocorticoid response elements (GRE) in the promotor regions of FASN and CD36 genes. The effects of DXM and LG on the expression of FASN and CD36 were determined by real-time quantitative reverse transcription PCR (RT-qPCR), western blot (WB) and immunohistochemical (IHC) analyses. The NAFLD induced by high-fat diet (HFD) and DXM was manifested by increased levels of liver enzymes, deterioration of histological architecture of the liver tissue and accumulation of fat droplets. Computational analysis revealed that the promotor regions of FASN and CD36 harper several GRE. Most importantly, treatment with DXM decreased phosphorylated adenosine monophosphate-activated protein kinase (p-AMPK) levels, while LG upregulate it. In addition, treatment with DXM increased expression of FASN and CD36 , whereas LG ameliorated these effects in a dose-dependent manner. DXM-induced NAFLD is mediated by upregulation of FASN and CD36 expression which may be attributed to GRE. LG coupling with DXM mitigates this induction by downregulating FASN and CD36 levels and therefore mitigates the development of NAFLD.

Investigation of flow interaction and the impact on flame propagation in an annular combustor with centrally staged burners - Hui Wang; Zhixin Zhu; Elsayed Barakat; Jing Hou; Haroun Hassan; Jing Liu; Wen Zeng; Wenjie Tao; Gaofeng Wang (Fuel, 2025)

Exploring neuro-glial interaction mechanisms in myelin plasticity for learning and memory enhancement - Reham M. Wahid; Nancy Husseiny Hassan; Walaa Samy; Aliaa Talaat; Amira Mokhtar Gobran; Shaimaa R. Abdelmohsen; Heba Atef Elsayed (Journal of Molecular Histology, 2025)

Limettin and PD98059 Mitigated Alzheimer’s Disease Like Pathology Induced by Streptozotocin in Mouse Model: Role of p-ERK1/2/p-GSK-3β/p-CREB/BDNF Pathway - Rofida M. Hassan; Nesrine S. Elsayed; Naglaa Assaf; Barbara Budzyńska; Krystyna Skalicka-Wożniak; Sherehan M. Ibrahim (Journal of Neuroimmune Pharmacology, 2025)
Sporadic Alzheimer’s disease (SAD) represents one of the major memory deficits that is characterized by tau hyperphosphorylation and amyloid beta (Aβ) deposition in the brain. Both are considered AD hallmarks which are mediated through neuroinflammation, oxidative stress, and cholinergic circuit interruption. This study aimed to show how limettin and PD98059 exert a neuroprotective effect against SAD and the possible role of the extracellular regulated kinase ( p- ERK1/2) and glycogen synthase kinase-3 beta ( p- GSK-3β) (Ser9)/cAMP-response element binding protein ( p- CREB) (Ser133)/brain derived neurotrophic factor (BDNF) pathway. Control animals (Group I) received the vehicles, group II received PD98059 (10 mg/kg/i.p), while group III was administered limettin (15 mg/kg/i.p). Additionally, the other three groups received a single dose of streptozotocin (STZ; 3 mg/kg/ICV), where group IV served as the SAD group, while groups V and VI received PD98059 and limettin daily for 3 weeks, respectively. The SAD animals receiving PD98059 and limettin increased the number of arm entries, % alternations in Y-maze, with reduction in mean escape latency, increase in time spent in target quadrant and platform crossing in Morris Water Maze, compared to the SAD group. Additionally, PD98059 and limettin administration to the STZ group downregulated persistent activation of p -ERK1/2 which in turn increased p -GSK-3β (Ser9), leading to enhanced p- CREB (Ser133) and BDNF expressions, as well as reducing inflammatory markers viz ., nuclear factor-kappa B and interleukin-6, leading to decreased Aβ deposition. Both treatments reduced immunohistochemical p -tau expression, brain edema, and increased intact neuron cells remarkably. Thus, based on these findings, PD98059 and limettin may have promising effects in protecting against SAD. Using blockers/inhibitory molecules are recommended to confirm effect through the corresponding pathway.

The potential of bone marrow derived mesenchymal stem cells in treating cisplatin induced sensorineural hearing loss in a guinea pig animal model - Mohamed Hassan Ali Elsayed Abdelwahed; Mohamed Hussien Badreldin; Ibrahim Hassan Ibrahim; Reham Farouk Zittoon; Rania A. Galhom; Sally S. Mohammed; Yehia Mohamed Ashry (Tissue and Cell, 2025)

Efficacy of curcumin-selenium nanoemulsion in alleviating oxidative damage induced by aluminum chloride in a rat model of Alzheimer’s disease - Safaa M. Awad; Yasser A. Attia; Hassan ElSayed; Shams H. Abdelhafez; Akaber T. Keshta; Eman Rashad; Heba M. A. Khalil; Aziza T. Fathy (Journal of Molecular Histology, 2025)

Alogliptin attenuates testicular damage induced by monosodium glutamate in both juvenile and adult male rats by activating autophagy: ROS dependent AMPK/mTOR - Manal Mohammad Morsy; Heba A. Hassan; Reham M. Morsi; Ola Elsayed Nafea; Azza I. Farag; Rania Saad Ramadan (Reproductive Toxicology, 2025)

Vinpocetine and Lactobacillus Attenuated Rotenone-Induced Parkinson’s Disease and Restored Dopamine Synthesis in Rats through Modulation of Oxidative Stress, Neuroinflammation, and Lewy Bodies Inclusion - Hanan M. Hassan; Hadeer O. Abou-Hany; Ahmed Shata; Doaa Hellal; Ahmed M. El-Baz; Zeinab H. ElSaid; Amira A. Haleem; Nesreen Elsayed Morsy; Rawan M. Abozied; Bassant M. Elbrolosy; Sally Negm; Attalla F. El-kott; et al. (Journal of Neuroimmune Pharmacology, 2025)

Dietary deacetylated chitin nanoparticles confer protection against diazinon toxicity in male African catfish: evaluation of immune-biochemical, antioxidant, and reproductive profiles - Hiam Elabd; Heba H. Mahboub; Heba S. Hamed; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Samar Kamel; Amany Ramah; Sahar H. Orabi; Sherif M. Shawky; Simon J. Davies; Zeinab Hassan (Fish Physiology and Biochemistry, 2025)

A novel strategy for enhancing high solid anaerobic digestion of fecal slag and food waste using percolate recirculation and dosage of nano zero-valent iron - Hamza Hassan Yusuf; Pan Xiaofang; Zhi-Long Ye; Taha Abdelfattah Mohammed Abdelwahab; Ahmed Elsayed Mahmoud Fodah (Water Research, 2024)

Rosuvastatin repurposing for prophylaxis against ethanol-induced acute gastric ulceration in rats: a biochemical, histological, and ultrastructural perspective - Hanan I. El-kerdasy; Eman Mohamed Faruk; Dina Allam Abdelmaksoud Hassan; Ola Elsayed Nafea; Fatma Ibrahim; Rania Abubaker Bagabir; Hala Magdy Anwer; Amany M. Allam (Inflammopharmacology, 2024)

Toxicological insight of magnetite nanogel: neuro-ethological, hepato-renal, antioxidant, and histopathological traits in Clarias gariepinus - Samar Kamel; Shaimaa A. A. Ahmed; Asmaa Elsayyad; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Mohamed Shaalan; Mohamed M. S. Gaballa; Heba H. Mahboub; Tarek Khamis; Sameh H. Ismail; Simon J. Davies; Zeinab Hassan (Aquaculture International, 2024)
Assessment of acute toxicity of magnetic nanogel (MNG) is crucial to conclude the safe applicable dose and to warrant its application in aquaculture. Therefore, the current study is a novel step to assess behavior, neuro-stress response, hepato-renal, oxidative, and histopathological variations produced by MNG’ acute toxicity in Clarias gariepinus . Two experiments were conducted: the first was a determination of the 96-h lethal concentration 50 (LC 50 ) of MNG in C. gariepinus . Meanwhile, the second was an assessment of the toxicological impacts of three different concentrations of MNG in C. gariepinus following a 10-day exposure period and a subsequent 10-day depuration trial. One hundred and eighty fish were allotted to four groups exposed to 0, 1/10, 1/8, or 1/5 96-h LC 50 of MNG. The outcomes exhibited that 96-h LC 50 of MNG for C. gariepinus was 44 mg/L. The subjected group to MNG induced a concentration-dependent elevation in the serum values of cortisol, alanine transaminase, aspartate transaminase, urea, and creatinine following MNG exposure. Marked elevation in the oxidative stress indicators (catalase (CAT), glutathione S-transferase activity (GST), and superoxide dismutase (SOD)) was also evident. Meanwhile, the value of the neurological biomarker, acetylcholinesterase (AChE), was markedly reduced in a concentration-dependent way. These biochemical changes were complemented by pathological alterations in the hepato-renal architecture. Interestingly, in response to the 10-day depuration period, most of the tested parameters were eliminated in C. gariepinus exposed to 1/10 of LC 50 . Conclusively, MNG can induce numerous adverse effects only at higher doses (1/5 and 1/8 of LC 50 ). Meanwhile, the lowest tested concentration of MNG (1/10 of LC 50 ) was safe for application in aquaculture practices with only mild disruptions in the bio-indices. In addition, a retrieval period of 10 days was sufficient to renovate these alterations only in fish exposed to the same concentration.

Dietary Nannochloropsis oculata could ameliorate cadmium chloride-induced reproductive toxicity in Barki rams: Antioxidant, MAP3K8, and inflammatory pathways - Doaa H. Elsayed; Ahmed Elaswad; A.S. EL-Hawy; M.F. El-Bassiony; Heba M.A. Abdelrazek; Fouda W.A.; Shady T. Hassan (Small Ruminant Research, 2024)

Angiotensin II Type 1 receptor blockade attenuates the neuropathological changes in the spinal cords of diabetic rats with modulation of nuclear factor erythroid 2-related factor 2/ heme oxygenase 1 system - Hassan Reda Hassan Elsayed; Eyad Mohamed Tolba Ali; Mohammed Rami Rabei; Eman Mohamad El Nashar; Mansour Abdullah Alghamdi; Norah Saeed Al-Zahrani; Shaker Hassan Alshehri; Rashid A. Aldahhan; Amira Ibrahim Morsy (Tissue and Cell, 2024)

The Influence of Lactobacillus spp. Secondary Metabolites Isolated from Immature Egyptian Honey on Human Pathogens, Transcription of Virulence Genes and Lung Cancer - Tarek R. Elsayed; Eman Nour; Ahmed A. Hamed; Ashwak Abdel-Moneim Hassan; Yasser Essam Elenany (Indian Journal of Microbiology, 2024)
This work aimed to isolate, and identify Lactic Acid Bacteria LAB from Egyptian immature citrus honey, and characterize their secondary metabolites, as well as determine the antibacterial activities and transcription of virulence genes (stx1, stx2, and eae) influenced by these bacterial secondary metabolites. From twenty hives, twenty immature citrus bee honey samples were taken. Traditional cultural and biochemical testing were used, followed by molecular confirmation. Further, LAB isolates' antibacterial and cytotoxic properties were investigated. 16S rRNA gene sequencing were assessed and, two lactic acid bacterial isolates were identified as Lactobacillus acidophilus Ch 2 and Levilactobacillus brevis Ch 1 . Both isolates have good antagonistic action against clinical pathogens, with Levilactobacillus brevis Ch 1 exhibiting the best antibacterial activity against all indicator pathogens examined. When compared to untreated cancer cells, the isolates demonstrated significant cytotoxic activity. Ch 1 and Ch 2 cell viability percentages were 39.5% and 18.76%, respectively. Furthermore, when exposed to Levilactobacillus brevis Ch 1 metabolites, Shiga-producing Escherichia coli (STEC) virulence gene expression was suppressed. To identify bacterial secondary metabolites, a high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (HPLC-QTOF) approach was developed. Twenty-seven metabolites from diverse chemical classes were discovered in the crude extracts with antibacterial and anticancer characteristics. This is the first thorough investigation on the metabolic profile of LAB isolated from immature Egyptian honey and the findings suggested that isolates or their secondary metabolites could be used in the food sector as medicinal alternatives or as a biocontrol agent.

The role of stinging nettle (Urtica dioica L.) in the management of rotenone-induced Parkinson's disease in rats - Emad Albadawi; Ahmed El-Tokhy; Muayad Albadrani; Mohammed Adel; Randa El-Gamal; Wael Zaarina; Mosaab Salah El-din El-Agawy; Hassan Reda Hassan Elsayed (Tissue and Cell, 2024)

Evaluating the impact of artificial maturation on the petrophysical and geochemical properties of unconventional shale formations by integrating dielectric and NMR measurements - Amjed Hassan; Mahmoud Elsayed; Ali Oshaish; Salah Al-Ofi; Ammar El-Husseiny; Israa S. Abu-Mahfouz; Mohamed Mahmoud; Mohamed Abouelresh; Hussein Attia (International Journal of Coal Geology, 2024)

The immunosuppressive, growth-hindering, hepatotoxic, and oxidative stress and immune related-gene expressions-altering effects of gibberellic acid in Oreochromis niloticus: A mitigation trial using alpha-lipoic acid - Walaa El-Houseiny; Ahmed H. Arisha; Amany Behairy; Mohamed M.M. Metwally; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Simon J. Davies; Bayan A. Hassan; Yasmina M. Abd-Elhakim (Pesticide Biochemistry and Physiology, 2024)

Applicability of Utilizing Remote Sensing Rainfall Products Data in Arid and Semi-Arid Poorly Gauged Catchments: Study of Wadi Ghoweiba Watershed, Egypt - Elsayed M. Abu El Ella; Abdullah A. Abbas; Hassan I. Mohamed (Journal of the Indian Society of Remote Sensing, 2024)
Due to the scarcity of established rain gauge stations, obtaining continuous time series daily rainfall observation data is a major challenge. The availability of these data is very essential to conduct hydrological studies and predicting flood events. Nowadays, several satellites could be used to provide such data. This study aims to investigate the appropriate remote sensing (RS) rainfall product and use its data to develop frequency analysis and intensity–duration–frequency curve (IDF curve) at 5-, 10-, 25-, 50-, 100-, and 200-year return periods in the study area. The evaluation of the PERSIANN family products (PERSIANN, PERSIANN-CCS, PERSIANN-CDR, and PDIR-Now) with NASA-POWER datasets compared to the available annual maximum of daily observation rainfall in Suez Rain Gauge (SRG) station as a reference was conducted. The results show that the PERSIANN-CDR product is the appropriate satellite-based rainfall dataset product based on the outcomes of the comparison criteria (RMSE, Bias, CC, and R 2 error measures) of rainfall characteristics analysis and Chi-squared test of distributions. The frequency analysis results confirmed that the values of about 30.3–38.6 and 40–53.3 mm/day corresponding to the biggest flood reported in 1965 and 2020 in SRG station and PERSIANN-CDR product have a return period of 50–100 years, classifying it as an extreme event in Wadi Ghoweiba. These findings would considerably benefit decision-makers in estimating flood risks and planning the appropriate structure protections in the Wadi Ghoweiba Watershed.

A new method for fault identification in real-time integrity monitoring of autonomous vehicles positioning using PPP-RTK - Hassan Elsayed; Ahmed El-Mowafy; Kan Wang (GPS Solutions, 2024)

Evaluation and performance comparison of different models for global solar radiation forecasting: a case study on five cities - Mohamed A. Ali; Ashraf Elsayed; Islam Elkabani; M. Elsayed Youssef; Gasser E. Hassan (Environment, Development and Sustainability, 2023)
Recently, solar energy has emerged as the most promising renewable energy source to meet the world’s energy demands. However, to harness the potential of solar energy, accurate data on solar radiation are crucial. It is considered the first step in assessing solar resources for various applications and achieving energy sustainability goals. Due to the unavailability of solar radiation measurements in many parts of the world, several models have been developed to predict global solar radiation (GSR) at these locations. Thus, this study aims to evaluate the proficiency of several GSR models at five new locations and determine the most suitable one for GSR prediction. The study has further developed solar radiation models for these new locations, as well as general ones for the entire region, which does not have any GSR models despite the existence of many planned solar energy facilities in this area. Additionally, the study investigates the effect of changing the length of the validation dataset on models’ performance and accuracy, as well as assesses the introduced models’ generalization capability. To achieve these objectives, the observed data of GSR for approximately 37 years at studied locations are used to develop and validate the proposed models. The study’s findings reveal that Model 1 provides the best performance at all locations, with accuracy, coefficient of determination ( $$R^{2}$$ R 2 ), ranging from 95 to 98%, except for the coastal location, where it is from 91 to 95%. The remaining performance indicators of the best models, such as RMSE, MABE, MAPE, and $$r$$ r , are good, and their values range from 0.7863 to 1.9097 (MJ m −2 day −1 ), from 0.6430 to 1.7060 (MJ m −2 day −1 ), from 3.4319 to 10.0890 (%), and from 0.9914 to 0.9981, respectively. The length of the validation dataset has a slight effect on the models’ performance, ranging from about 1% to 2%. Therefore, Model 1 is the recommended solar radiation model, which can provide precise and rapid estimates of global solar radiation. This approach could be used in the design and performance evaluation of many solar applications. The primary benefit of this approach in the current investigation is that temperature data are continuously and effortlessly recorded for various purposes.

Alpha-lipoic acid suppresses gibberellic acid nephrotoxicity in Nile tilapia (Oreochromis niloticus) via modulating oxidative stress, inflammation, cytokine production, and apoptosis - Walaa El-Houseiny; Ahmed H. Arisha; Mohamed M.M. Metwally; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Simon J. Davies; Bayan A. Hassan; Yasmina M. Abd-Elhakim (Pesticide Biochemistry and Physiology, 2023)

Metabolic profiling and cytotoxic activities of ethanol extract of Dypsis leptocheilos aerial parts and its green synthesized silver nanoparticles supported by network pharmacology analysis - Marwa Hassan Hussaen Mohammed; Ashraf Nageeb Elsayed Hamed; Sammar Fathy Elhabal; Fatma A. Mokhtar; Usama Ramadan Abdelmohsen; Mostafa Ahmed Fouad; Mohamed Salah Kamel (South African Journal of Botany, 2023)

A comparative analysis of second-generation biofuels and its potentials for large-scale production in arid and semi-arid regions - Yassir Makkawi; Muhammad Khan; Fatemeh Hassan Pour; Omar Moussa; Baraa Mohamed; Hamza Alnoman; Yehya Elsayed (Fuel, 2023)

Chemical composition and anti-proliferative activities of Hyophorbe lagenicaulis aerial parts and their biogenic nanoparticles supported by network pharmacology study - Marwa Hassan Hussaen Mohammed; Ashraf Nageeb Elsayed Hamed; Sammar Fathy Elhabal; Fatma A. Mokhtar; Usama Ramadan Abdelmohsen; Mostafa Ahmed Fouad; Mohamed Salah Kamel (South African Journal of Botany, 2023)

The Effect of Neonicotinoids Exposure on Oreochromis niloticus Histopathological Alterations and Genotoxicity - Islam M. El-Garawani; Elsayed A. Khallaf; Alaa A. Alne-na-ei; Rehab G. Elgendy; Hassan M. Sobhy; Adel Khairallah; Heba M. R. Hathout; Farag Malhat; Amany E. Nofal (Bulletin of Environmental Contamination and Toxicology, 2022)
This study aimed to examine the side effects of selected neonicotinoids (Acetamiprid, Aceta, and Imidacloprid, Imid) on Oreochromis niloticus juveniles. The acute toxicity, Probit method, revealed an LC 50 of 195.81 and 150.76 ppm for Aceta/96 h and Imid/72 h respectively. The fish were divided into three groups that were exposed, for 21 days (n = 5/replicate), to 1/10 of the LC 50 of either neonicotinoids, however, the third was an unexposed control group. Results of erythrocytic micronucleus (MN), and nuclear abnormalities (NA) showed that Aceta and Imid exposure caused a significant ( p < 0.05) increase in MN by ~ 2.2 and ~ 10 folds, respectively relative to control. NAs occurred at the order of kidney-shaped > budding > binucleated in Aceta, however, budding > binucleated > kidney-shaped was noticed in the Imid group. Histopathological changes in gills, liver, and muscles were observed significantly in both exposed groups with more severity in the Imid group. Collectively, Aceta and Imid have potential genotoxicity and histopathological alterations in O. niloticus .

Evaluation of the antineoplastic property of prodigiosins and 5-fluorouracil in restraining the growth of Ehrlich solid tumors in mice - Elsayed S. E. Hassan; Medhat W. Shafaa; Ahmed H. I. Faraag; Ehab Essawy; Ashraf A. Bakkar; Wafa A. AL-Megrin; Manal F. El-Khadragy; Mohamed S. Abdelfattah; Ahmed E. Abdel Moneim (Environmental Science and Pollution Research, 2022)

Hypoalbuminemia affects the spatio-temporal tissue distribution of ochratoxin A in liver and kidneys: consequences for organ toxicity - Reham Hassan; Adrian Friebel; Lisa Brackhagen; Zaynab Hobloss; Maiju Myllys; Daniela González; Wiebke Albrecht; Elsayed S. I. Mohammed; Abdel-latif Seddek; Rosemarie Marchan; Cristina Cadenas; Benedikt Cramer; et al. (Archives of Toxicology, 2022)
Hypoalbuminemia (HA) is frequently observed in systemic inflammatory diseases and in liver disease. However, the influence of HA on the pharmacokinetics and toxicity of compounds with high plasma albumin binding remained insufficiently studied. The ‘ lack-of-delivery-concept ’ postulates that HA leads to less carrier mediated uptake of albumin bound substances into hepatocytes and to less glomerular filtration; in contrast, the ‘ concept-of-higher-free-fraction ’ argues that increased concentrations of non-albumin bound compounds facilitate hepatocellular uptake and enhance glomerular filtration. To address this question, we performed intravital imaging on livers and kidneys of anesthetized mice to quantify the spatio-temporal tissue distribution of the mycotoxin ochratoxin A (OTA) based on its auto-fluorescence in albumin knockout and wild-type mice. HA strongly enhanced the uptake of OTA from the sinusoidal blood into hepatocytes, followed by faster secretion into bile canaliculi. These toxicokinetic changes were associated with increased hepatotoxicity in heterozygous albumin knockout mice for which serum albumin was reduced to a similar extent as in patients with severe hypoalbuminemia. HA also led to a shorter half-life of OTA in renal capillaries, increased glomerular filtration, and to enhanced uptake of OTA into tubular epithelial cells. In conclusion, the results favor the ‘ concept-of-higher-free-fraction ’ in HA; accordingly, HA causes an increased tissue uptake of compounds with high albumin binding and increased organ toxicity. It should be studied if this concept can be generalized to all compounds with high plasma albumin binding that are substrates of hepatocyte and renal tubular epithelial cell carriers.

Effects of dietary supplementation of chromium methionine chelate on growth performance, oxidative stress, hematological indices, and carcass traits of broiler chickens - Ibrahim M. I. Youssef; Ibrahim M. I. Abdo; Hassan F. A. Elsukkary; Magdy F. El-Kady; Magdy Elsayed (Tropical Animal Health and Production, 2022)
This study was conducted to evaluate the dietary effects of chromium methionine (Cr-Meth) chelate on growth performance, oxidative stress parameters, blood biochemistry, and carcass traits of broiler chickens. An experiment was conducted on 34,000 1-day-old straight-run broiler chicks (Indian River; 42.0 ± 0.03) at a commercial farm. The chicks were divided randomly into 3 groups; the first group contained 17,000 birds, which used as a control, whereas the second and third groups consisted of 7000 and 10,000 birds, respectively, with 5 replicates per group. A completely randomized design was used. The birds were fed the experimental diets containing graded levels of Cr-Meth chelate: 0 (control), 50, and 100 g/ton. This compound consisted of chromium (0.4%) chelated with methionine, and it supply the diets with 200 and 400 ppb Cr for the used levels of 50 and 100 g/ton feed, respectively. Growth performance indices (body weight, body weight gain, feed intake, and feed conversion ratio) were measured throughout the experiment. At the end of experiment, 10 birds per treatment were slaughtered, and the carcass yield with relative weight of the internal organs was determined. Also, blood samples were taken and analyzed for glutathione peroxidase activity, malondialdehyde, ALT, AST, total protein, albumin, glucose, urea, creatinine, triglycerides, and total cholesterol. It was found that Cr-Meth improved the body weight, weight gain, feed intake, and feed conversion ratio of broilers. Moreover, it reduced the mortality rate of birds. The chelated chromium can alleviate the oxidative status of birds by increasing the plasma glutathione peroxidase activity and reducing the serum malondialdehyde level. It was observed that the effects of 100 g/ton Cr-Meth chelate on performance indices, mortality rate, and oxidative stress parameters were better than that of 50 g/ton inclusion rate. Supplementation of Cr-Meth increased the total protein level, but reduced the glucose, total cholesterol, and triglyceride concentrations in the blood serum. In addition, it increased the carcass yield and reduced the abdominal fat percentage of the birds’ carcass. Therefore, chromium can be included in diets of broilers at a rate of 200 to 400 ppb, and the higher concentration was more effective than the lower one. So, it can be recommended to use Cr-Meth chelate in broiler diets at 100 g/ton to improve the productive performance and reduce the oxidative stress of birds.

Expression profiling of HSP 70 and interleukins 2, 6 and 12 genes of Barki sheep during summer and winter seasons in two different locations - Raed A. Abu Rawash; Mahmoud A. Sharaby; Gamal El-Din A. Hassan; Alaa E. Elkomy; Elsayed E. Hafez; Salma H. Abu Hafsa; Mohamed M. I. Salem (International Journal of Biometeorology, 2022)
The objectives of this research were to contrast the expression values of heat shock protein (HSP70) and interleukins 2, 6 and 12 (IL 2, IL 6 and IL 12) genes in summer and winter in two different locations in Egypt (Alexandria zone and Matrouh zone) to deduce changes in thermo-physiological traits and biochemical blood metabolites of Barki sheep. A total of 50 ewes (20 in Alexandria and 30 in Matrouh) were individually blood sampled to determine plasma total protein (TP), Albumin, Globulin and Glucose constituents and T3, T4 and cortisol hormones. The thermo-physiological parameters of rectal temperature (RT, °C), skin temperature (ST, °C), Wool temperature (WT, °C), respiration rate (RR, breaths/min) and pulse rate (PR, beats/min) were measured for each ewe. Expressions of IL 2, IL 6, IL 12 and HSP 70 in summer and winter were analyzed along with thermo-physiological parameters and blood biochemical metabolites. In both locations, THI had significant effects on ST, WT, PR and RR, but not significant on RT. However, it had no significant effects on blood plasma metabolites and hormonal concentrations in the two locations in summer and winter. In Alexandria location, THI had negative significant effect on the expressions of IL-2 and IL-6 but positively affected on HSP70 genes in winter, while the expression of IL-12 gene was not affected by seasons, whereas in Matrouh zone, the effects of THI on the expressions of all tolerance genes were not significant. The results of the current study suggest that IL-2, IL-6 and HSP70 genes could be used as molecular markers for heat/cold stress.

Characterization and Expression Analysis of Extradiol and Intradiol Dioxygenase of Phenol-Degrading Haloalkaliphilic Bacterial Isolates - Nasser H. Abbas; Afaf Elsayed; Hamdy A. Hassan; Sabha El-Sabbagh; Ashraf F. Elbaz; Hany Khalil (Current Microbiology, 2022)
Haloalkophilic bacteria have a potential advantage as a bioremediation organism of high oil-polluted and industrial wastewater. In the current study, Haloalkaliphilic isolates were obtained from Hamralake, Wadi EL-Natrun, Egypt. The phenotype script, biochemical characters, and sequence analysis of bacterial-16S rRNA were used to identify the bacterial isolates; Halomonas HA1 and Marinobacter HA2 . These strains required high concentrations of NaCl to ensure bacterial growth, especially Halomonas HA1 strain. Notably, both isolates can degrade phenol at optimal pH values, between 8 and 9, with the ability to grow in pH levels up to 11, like what was seen in the Halomonas HA1 strain. Moreover, both isolates represent two different mechanistic pathways for phenol degradation. Halomonas HA1 exploits the 1,2 phenol meta-cleavage pathway, while Marinobacter HA2 uses the 2,3 ortho-cleavage pathway as indicated by universal primers for 1,2 and 2,3 CTD genes. Interestingly, Marinobacter HA2 isolate eliminated the added phenol within an incubation period of 72 h, while the Halomonas HA1 isolate invested 96 h in degrading 84% of the same amount of phenol. Phylogenetic analysis of these 1,2 CTD (catechol dioxygenase) sequences clearly showed an evolutionary relationship between 1,2 dioxygenases of both Halomonadaceae and Pseudomonadaceae . In comparison, 2,3 CTD of Marinobacter HA2 shared the main domains of the closely related species. Furthermore, semi-quantitative RT-PCR analysis proved the constitutive expression pattern of both dioxygenase genes. These findings provide new isolates of Halomonas sp. and Marinobacter sp. that can degrade phenol at high salt and pH conditions via two independent mechanisms.

Mitigating effect of single or combined administration of nanoparticles of zinc oxide, chromium oxide, and selenium on genotoxicity and metabolic insult in fructose/streptozotocin diabetic rat model - Rasha M. Hassan; Mai Elsayed; Tahany E. Kholief; Naglaa H. M. Hassanen; Jehan A. Gafer; Yasser A. Attia (Environmental Science and Pollution Research, 2021)

TCF7L2 gene polymorphism as a risk for type 2 diabetes mellitus and diabetic microvascular complications - Noran Talaat Aboelkhair; Heba Elsayed Kasem; Amera Anwar Abdelmoaty; Rawhia Hassan El-Edel (Molecular Biology Reports, 2021)

Improvement of the sorption behavior of aluminum silicate composite toward 134Cs and 60Co radionuclides by non-living biomass of Chlorella vulgaris - Gehan Abdel Rahman Dakroury; Shereen Fathy Abo-Zahra; Hisham Soliman Hassan; Hamdy Elsayed Ahmed Ali (Environmental Science and Pollution Research, 2020)

Identification of serum N-glycoproteins as a biological correlate underlying chronic stress response in mice - Motamed Elsayed Mahmoud; Ibrahim F. Rehan; Kh. El-Dawy Ahmed; Amany Abdelrahman; Saeed Mohammadi; Ahmed F. Abou-Elnaga; Mohammed Youssef; Hassan Mahmoud Diab; Doaa Salman; Asmaa Elnagar; Hesham H Mohammed; Obeid Shanab; et al. (Molecular Biology Reports, 2019)

Method validation and evaluation of household processing on reduction of pesticide residues in tomato - Helmy Hassan; Elham Elsayed; Abd El-Rahman Abd El-Raouf; Salma N. Salman (Journal of Consumer Protection and Food Safety, 2019)

Immunological role of CD4+CD28null T lymphocytes, natural killer cells, and interferon-gamma in pediatric patients with sickle cell disease: relation to disease severity and response to therapy - Mohsen Saleh ElAlfy; Amira Abdel Moneam Adly; Fatma Soliman ElSayed Ebeid; Deena Samir Eissa; Eman Abdel Rahman Ismail; Yasser Hassan Mohammed; Manar Elsayed Ahmed; Aya Sayed Saad (Immunologic Research, 2018)

Evaluating interspecific wheat hybrids based on heat and drought stress tolerance - Mohamed I. Hassan; Elsayed A. Mohamed; Mahmoud A. El-rawy; Karam A. Amein (Journal of Crop Science and Biotechnology, 2016)

Micropropagation of Cattleya: Improved in vitro rooting and acclimatization - Yaser Hassan Dewir; Mohammed Elsayed El-Mahrouk; Hosakatte Niranjana Murthy; Kee Yoeup Paek (Horticulture, Environment, and Biotechnology, 2015)

Drought risk assessment using remote sensing and GIS techniques - Abdel-Aziz Belal; Hassan R. El-Ramady; Elsayed S. Mohamed; Ahmed M. Saleh (Arabian Journal of Geosciences, 2014)